Raised tone reveals ATP as a sympathetic neurotransmitter in the porcine mesenteric arterial bed - Shatarat, Amjad; Dunn, William R.; Ralevic, Vera (Springer Verlag, 2014)
The relative importance of ATP as a functional sympathetic neurotransmitter in blood vessels has been shown to be increased when the level of preexisting vascular tone or pressure is increased, in studies carried out in rat mesenteric arteries. The aim of the present study was to determine whether tone influences the involvement of ATP as a sympathetic cotransmitter with noradrenaline in another species. We used the porcine perfused mesenteric arterial bed and porcine mesenteric large, medium and small arteries mounted for isometric tension recording, because purinergic cotransmission can vary depending on the size of the blood vessel. In the perfused mesenteric bed at basal tone, sympathetic neurogenic vasocontractile responses were abolished by prazosin, an α1- adrenoceptor antagonist, but there was no significant effect of α,β-methylene ATP, a P2X receptor-desensitizing agent. Submaximal precontraction of the mesenteric arterial bed with U46619, a thromboxane A2 mimetic, augmented the sympathetic neurogenic vasocontractile responses; under these conditions, both α,β-methylene ATP and prazosin attenuated the neurogenic responses. In the mesenteric large, medium and small arteries, prazosin attenuated the sympathetic neurogenic contractile responses under conditions of both basal and U46619-raised tone. α,β-Methylene ATP was effective in all of these arteries only under conditions of U46619- induced tone, causing a similar inhibition in all arteries, but had no significant effect on sympathetic neurogenic contractions at basal tone. These data show thatATP is a cotransmitter with noradrenaline in porcine mesenteric arteries; the purinergic component was revealed under conditions of partial precontraction, which is more relevant to physiological conditions.